PENERAPAN STATISTIKA DALAM SISTEM INFORMASI - Nuraini Sri Bina (MES: Journal of Mathematics Education and Science, 2020)
Statistics is a science that deals with data. Starting from the data collection stage to drawing conclusions on the data studied in statistics. The concepts in statistics are widely applied in various fields and organizations to help analyze data and inform the public. Statistics as one of the sciences that has the ability to accurately estimate or estimate the condition of a data is a science that is difficult to separate in general technological developments. Development in the field of information technology cannot be separated from the role of statistics. On this occasion, he explained about the application of statistics in the development of information systems technology. Described in detail how closely the science of statistics and the application of various statistical concepts in the development of information systems.